Analysis of the mechano‑acoustic influence of the tympanic cavity in the auditory system - García-González, Antonio; Castro Egler, Cristina; González-Herrera, Antonio (BMC, 2016)
The main objective of this paper is to study the mechanical influence of the tympanic cavity (TC) in the auditory system (AS). It is done for a frequency range from 0.1 to 20 kHz and the pressure source was applied in the external ear canal (EEC) entrance. Numerical simulations were developed for seven different models by means of finite element model. On the basis of an EEC finite elements model, the addi tional elements are coupled and removed in order to evaluate the contribution of the TC. Tympanic membrane, ossicular chain, simplified cochlea and TC were modeled and simulated in four different combinations. Pressure, velocity, and displacement measures were obtained in AS key points in order to be compared with experimental results. Umbo and stapes transfer functions have been represented. The main conclusion is that we find evidence that the presence of the TC in the AS introduces a second resonance in middle ear transfer functions at frequencies above 3 kHz.
Keywords: Oído; Audición - Simulación por ordenador; Ear canal; Middle ear; Tympanic membrane; Tympanic cavity; Finite element analysis; Resonance